2016
DOI: 10.1152/ajpheart.00378.2016
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic neural reactivity to mental stress in offspring of hypertensive parents: 20 years revisited

Abstract: Fonkoue IT, Wang M, Carter JR. Sympathetic neural reactivity to mental stress in offspring of hypertensive parents: 20 years revisited. Am J Physiol Heart Circ Physiol 311: H426 -H432, 2016. First published July 1, 2016; doi:10.1152/ajpheart.00378.2016.-A number of recent studies have highlighted large interindividual variability of muscle sympathetic nerve activity (MSNA) responsiveness to mental stress in humans. The purpose of this study was to examine blood pressure (BP) and MSNA responsiveness to mental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
3
17
0
Order By: Relevance
“…A recent study by Fonkoue et al . () substantiates and extends these findings, with reports of greater elevations in MSNA during mental stress in those with a family history of hypertension than those without, despite no differences in the blood pressure responses between groups. Although the effect of mental stress on MSNA has been the focus of a number of studies over the past 40 years, many research groups have reported increases in MSNA in response to laboratory mental stressor tasks (Kuniyoshi et al .…”
Section: Introductionsupporting
confidence: 71%
“…A recent study by Fonkoue et al . () substantiates and extends these findings, with reports of greater elevations in MSNA during mental stress in those with a family history of hypertension than those without, despite no differences in the blood pressure responses between groups. Although the effect of mental stress on MSNA has been the focus of a number of studies over the past 40 years, many research groups have reported increases in MSNA in response to laboratory mental stressor tasks (Kuniyoshi et al .…”
Section: Introductionsupporting
confidence: 71%
“…; Fonkoue et al . ). We previously reported exaggerated pressor and sympathetic responses during the last minute of submaximal static handgrip in young women +FH (Greaney et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Fonkoue et al . ), suggest this concept may warrant further investigation. We agree with Park et al .…”
mentioning
confidence: 94%
“…; Fonkoue et al . ), giving rise to a ‘sympathetic reactivity hypothesis’ (Fonkoue et al . ) that parallels the ‘cardiovascular reactivity hypothesis’, which suggests that heightened haemodynamic responses to acute laboratory mental stress provide a unique window into future risk of hypertension.…”
mentioning
confidence: 99%
See 1 more Smart Citation